Baseline blood eosinophil count as a predictor of treatment response to the licensed dose of mepolizumab in severe eosinophilic asthma. (November 2019) - Albers, Frank C.; Licskai, Christopher; Chanez, Pascal; Bratton, Daniel J.; Bradford, Eric S.; Yancey, Steven W.; Kwon, Namhee; Quirce, Santiago
Abstract: Background: Previous analyses examining the relationship between blood eosinophil count and mepolizumab treatment effects in severe eosinophilic asthma have used a range of doses and administration routes. Methods: This post hoc meta-analysis included data from the MENSA (MEA115588/NCT01691521) and MUSCA (200862/NCT02281318) trials. Patients (≥12 years) with severe eosinophilic asthma who experienced ≥2 exacerbations in the prior year received either mepolizumab 100 mg subcutaneously (SC) or 75 mg intravenously, or placebo plus standard of care every 4 weeks. This meta-analysis reports data from patients receiving the licensed dose of mepolizumab (100 mg SC) or placebo only. The primary endpoint was the annual rate of clinically significant exacerbations; secondary endpoints included rate of exacerbations requiring hospitalization/emergency room (ER) visit, proportion of patients with no clinically significant exacerbations, and changes from baseline in forced expiratory volume in 1 s, Asthma Control Questionnaire-5 and St George's Respiratory Questionnaire scores. Analyses were stratified by baseline blood eosinophil count (<150, ≥150, ≥300, ≥400, ≥500, ≥750, ≥1000, ≥150–<300, or ≥300–<500 cells/μL). Results: Mepolizumab reduced annual clinically significant exacerbation rates by 45%–85%, exacerbations requiring hospitalization/ER visit by 60%–70%, and increased the odds of no clinically significant exacerbations across all eosinophil threshold subgroups versus placebo, and improved all other secondary endpoints in subgroups ≥150 cells/μL. Greater treatment effects with increasing blood eosinophil count were observed. Conclusions: Mepolizumab demonstrated consistent clinical benefits in patients with baseline blood eosinophil counts ≥150 cells/μL, confirming the suitability of this cut-off for identifying patients responsive to the licensed mepolizumab dose. Highlights: Mepolizumab is effective at blood eosinophil counts ≥150 cells/μL in severe asthma. Higher baseline blood eosinophil counts lead to greater mepolizumab response vs PBO. A blood eosinophil count threshold ≥150 cells/μL selects mepolizumab responders.